Respuesta :

Answer:

Step-by-step explanation:

  [1]    3x - 4y = -24

  [2]    -x - 16y = -52

Graphic Representation of the Equations :

   -4y + 3x = -24        -16y - x = -52  

 

Solve by Substitution :

// Solve equation [2] for the variable  x

 [2]    x = -16y + 52

// Plug this in for variable  x  in equation [1]

  [1]    3•(-16y+52) - 4y = -24

  [1]     - 52y = -180

// Solve equation [1] for the variable  y

  [1]    52y = 180

  [1]    y = 45/13

// By now we know this much :

   x = -16y+52

   y = 45/13

// Use the  y  value to solve for  x

   x = -16(45/13)+52 = -44/13

Solution :

{x,y} = {-44/13,45/13}

ACCESS MORE